2017
DOI: 10.1186/s40734-016-0048-5
|View full text |Cite
|
Sign up to set email alerts
|

Lessons I have learned from my patients: everyday life with primary orthostatic tremor

Abstract: BackgroundPrimary orthostatic tremor is a rare disorder that is still under-diagnosed or misdiagnosed. Motor symptoms are fairly characteristics but the real impact on the patient’s every day life and quality of life is under-estimated. The ”how my patients taught me” format describes the impact on the patients’ every day life with their own words, which is rarely done.Case presentationA 46 year old lady was diagnosed primary orthostatic tremor (POT) based on the cardinal symptoms: feelings of instability, leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…[10][11][12] Longitudinal observations have indicated that OT is a progressive disorder, 13 which may be associated with a number of non-motor symptoms such as depression and cognitive impairment. 14,15 Moreover, patients with OT have a markedly reduced quality of life. 16 Hence, the pathological underpinnings of this complex disorder need to be understood so that specific therapeutic avenues may be explored and better treatments implemented.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Longitudinal observations have indicated that OT is a progressive disorder, 13 which may be associated with a number of non-motor symptoms such as depression and cognitive impairment. 14,15 Moreover, patients with OT have a markedly reduced quality of life. 16 Hence, the pathological underpinnings of this complex disorder need to be understood so that specific therapeutic avenues may be explored and better treatments implemented.…”
Section: Introductionmentioning
confidence: 99%
“…While instability on standing and tremor are hallmarks of this disorder, symptoms such as fear of falling, social phobia, anxiety, and depression are also common and cause significant morbidity. 5 Due to its rare nature, there has been a dearth of well-designed randomized controlled trials. 2 Of the medications that have been trialed, clonazepam has been shown to be the most beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic PD affects approximately 0.3% of the entire general population and 1% of the general population over the age of 60 years [ 9 ]. Among the GD1 patient population, PD is estimated to be present in 4% of all patients [ 10 ]. Patients with GD1 also have a lower mean age of onset of parkinsonian symptoms relative to the general population: 48 years of age in comparison to 71 years, respectively [ 11 ].…”
Section: Introductionmentioning
confidence: 99%